Capital Market Reaction Analysis Before and After Bank Indonesia's Decision Regarding Interest Rates : Analisis Reaksi Pasar Modal Sebelum Dan Sesudah Keputusan Bank Indonesia Mengenai Suku Bunga - Putri Yuliean Fajarwati; Nurasik (Academia Open, 2020)
The development of capital market activities can not be separated from the role of investors as investors and disclosure of information as consideration of investor decision making.This research aims to find out how the capital market reacts before Bank Indonesia's decision on interest rates.And to find out how the capital market reacted after Bank Indonesia's decision on interest rates.This research uses quantitative research that is event study. Data collection of financial statements at the Investment Gallery of the Indonesia Stock Exchange, University of Muhammadiyah Sidoarjo.The population in this study includes LQ45 companies that have been listed on the Indonesia Stock Exchange, with sampling techniques namely total sampling.Data analysis using T-test. The results of this study prove that there is a difference in the average abnormal return before and after Bank Indonesia's decision on interest rates as evidenced by the value of Sig.(2-tailed) is 0.000 less than 0.005 and there is a difference in average trading volume activity before and after Bank Indonesia's decision on interest rates as evidenced by the value of Sig.(2-tailed) 0.000 less than 0.005.